2021
DOI: 10.1038/s41598-021-02668-3
|View full text |Cite
|
Sign up to set email alerts
|

Wheat (Triticum aestivum) adaptability evaluation in a semi-arid region of Central Morocco using APSIM model

Abstract: In this study, we evaluated the suitability of semi-arid region of Central Morocco for wheat production using Agricultural Production Systems sIMulator (APSIM) considering weather, soil properties and crop management production factors. Model calibration was carried out using data collected from field trials. A quantitative statistics, i.e., root mean square error (RMSE), Nash–Sutcliffe efficiency (NSE), and index of agreement (d) were used in model performance evaluation. Furthermore, series of simulations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Process-based physiological and ecological models simulate crop growth, development, and water and nutrient uptake. They can explore the dynamic relationships among atmosphere, crop, and soil and enable the prediction of crop responses to climate, genotype, farm management, and their interactions ( Briak and Kebede, 2021 ). Prior studies focused on crop variety parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Process-based physiological and ecological models simulate crop growth, development, and water and nutrient uptake. They can explore the dynamic relationships among atmosphere, crop, and soil and enable the prediction of crop responses to climate, genotype, farm management, and their interactions ( Briak and Kebede, 2021 ). Prior studies focused on crop variety parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Process-based crop models are often used to study the effects of genetics, field management, and their interactions on wheat growth and development as well as the impact of climate warming on wheat productivity. Briak and Kebede (2021) used their experimental data to calibrate and evaluate the Agricultural Production Systems Simulator (APSIM-Wheat) model and demonstrated its accuracy. Their simulation experiments showed that optimal sowing dates for suitable wheat varieties improve crop adaptation to climate warming.…”
Section: Introductionmentioning
confidence: 99%
“…A mixed model is a powerful statistical tool that examines the relationships between observed responses and explanatory covariates while accounting for two types of varia-tions [80]. By incorporating fixed and random effects, it captures systematic influences and inherent data variability [81].…”
Section: Application Of Linear Mixed-effects Modelsmentioning
confidence: 99%
“…The study focuses on evaluating different sowing mechanical tillage methods for wheat production, where conventionally chosen methods depend on input costs such as tillage and fuel costs, and grain yield, to control economic bene ts Briak et al, 2021;Chellappa et al, 2021;Daloz et al, 2021;Poudel et al, 2021;Radmehr et al, 2022). To reduce tillage costs and increase pro tability, zero tillage technique with rice residue mulching was implemented for timely sowing of wheat.…”
Section: Introductionmentioning
confidence: 99%